A dictionary of locutons from liturgical books by protopriest A. I. Nevostruev (понасилую — посредѣ) - Maria Davydenkova; Nadezhda Kaluzhnina; Maria Strievskaya; Olga Strievskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The “Dictionary of Locutions from Liturgical Books” by Protopriest A. Nevostruev, completed in the middle of the 19th century and never published, can be regarded both as a significant achievement of Church Slavonic studies and as a valuable lexicographic source. The manuscript is kept in the Russian State Library. The decrepit state of the manuscript has determined the necessity of its urgent study and edition. The significance of this project is primarily due to the fact that the text of the dictionary is being made accessible to linguists for the first time. The orthography and grammar of the dictionary reflect the linguistic views of the time of its creation and can be of interest for those who study the history of Russian linguistics. This paper contains the 6th part of dictionary entries beginning in letter P. The characteristic features of the publication of this Dictionary, the lists of sources, abbreviations and symbols were described in detail in the previous issues of St. Tikhon’s University Review. All previously published parts of the Dictionary together with the critical apparatus can be found at the website of St. Tikhon’s University for the Humanities